An Experimental Investigation on the Performance of a Double Slope Single-Stage Solar Still tested in Cape Town, South Africa - Pangwa, Nandipha; Msomi, Velaphi (Engineering, Technology & Applied Science Research, 2025)
Desalination systems have emerged as an alternative solution to the global water crisis, with many countries using them to alleviate freshwater scarcity. Various types of desalination systems exist, including solar desalination, which is the focus of this study. This research aimed to design, construct, and test a Double Slope Single-Stage Solar Still (DSSSSS) under real environmental conditions in Cape Town, South Africa. The system incorporated an Evacuated Tube Solar Collector (ETSC) to enhance its performance. The DSSSSS was tested during day and night. The experiment took place in October and November 2023, during the spring season in South Africa. The water depth was maintained at 50 mm using a float valve, and a 220 V water circulation pump ensured continuous seawater flow between the basin and the ETSC. The system was tested for 12 days, the highest production obtained per day was 513 ml on a day when the maximum outdoor temperature was 30 oC. The minimum distillate produced was 140 ml on a day that had a maximum temperature of 22 oC and that was one of the coldest days during the testing period. A total of 2142 ml of distillate was produced during daytime and 1679 ml at night, amounting to 3821 ml over the testing period. Salinity and conductivity tests were conducted on both the raw seawater and the distillate to compare water quality before and after the purification process.